Challenges Facing People-Driven Development in the Context of a Strong, Delivery-Oriented State: Joe Slovo Village, Port Elizabeth - Huchzermeyer, Marie (Springerlink. Urban Forum, Vol. 17, No. 1, January-March 2006., 2006)
The Joe Slovo settlement process on the outskirts of Port Elizabeth in the Eastern Cape was, in the first instance, about securing land and housing for a large number of desperate people, living in intolerable conditions that are now internationally referred to as ‘slums’ (see UN-Habitat, 2003) (Figure 1). In the international context of the Millennium Development Goal 7 Task 11 to significantly improve the lives of 100 million ‘slum’ dwellers by 2020 (United Nations, 2000), and the South African response through a new human settlement plan (Department of Housing, 2004), the Joe Slovo case gives important insight into the complex interface between organised low-income households, in this case members of the Homeless People’s Federation, actively engaging in mproving their living conditions, and government’s housing delivery and urban governance machinery.
Keywords: Joe Slovo Village, Port Elizabeth; securing land; low-income households; slums; government’s housing delivery; urban governance machinery.